2010
DOI: 10.2478/abm-2010-0039
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of microvascular density and proliferation index in undifferentiated nasopharyngeal carcinoma

Abstract: Background: Undifferentiated nasopharyngeal carcinoma is a highly malignant tumor with an endemic distribution. Several histologic parameters have been studied to provide prognostic information for patient management. Both proliferation index and microvascular density are commonly determined on such tumors, but the relationship between these two parameters has not been studied fully. Objectives: Determine the association between microvascular density and cellular proliferation in undifferentiated nasopharyngea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 26 publications
1
16
0
2
Order By: Relevance
“…Beberapa penelitian di berbagai negara juga menunjukkan penderita KNF laki-laki lebih banyak daripada perempuan dengan rata-rata perbandingan 2-3:1. [20][21][22][23] Tipe histopatologi terbanyak adalah non keratinizing squamous cell carcinoma. Ukuran tumor primer terbanyak dijumpai pada penelitian ini adalah T4.…”
Section: Diskusiunclassified
See 1 more Smart Citation
“…Beberapa penelitian di berbagai negara juga menunjukkan penderita KNF laki-laki lebih banyak daripada perempuan dengan rata-rata perbandingan 2-3:1. [20][21][22][23] Tipe histopatologi terbanyak adalah non keratinizing squamous cell carcinoma. Ukuran tumor primer terbanyak dijumpai pada penelitian ini adalah T4.…”
Section: Diskusiunclassified
“…Sebaiknya ketiga antigen dibandingkan pada jaringan karsinoma yang akan diperiksa sebelum menentukan jenis antigen mana yang lebih baik. Kelemahan pada penelitian ini adalah tidak dilakukan perbandingan penggunaan ketiga jenis antibodi, mengingat besarnya biaya reagen antibodi, disamping itu Taweevisit et al 23 pada penelitiannya terhadap jaringan karsinoma nasofaring menemukan bahwa CD31 adalah antibodi yang terbaik memberikan pewarnaan terhadap pembuluh darah, dan mewarnai latar belakang lebih sedikit dan tidak mewarnai selsel lain. Ini yang menjadi alasan pemilihan CD31 pada penelitian ini.…”
Section: Diskusiunclassified
“…Several studies have shown that the p53 protein was overexpressed in many cases of NPC as detected by immunochemistry [ 19 - 21 ]. This is further supported by the work in our laboratory which showed that p53 protein was found to be accumulated in 58 NPC biopsy samples formalin-fixed, paraffin-waxed embedded tissues of Malaysian patients but the p53 gene was not mutated at the p53 mutation hot-spots Exons 5-8 [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the comparison of subjects with male and female gender was 2.7:1 ( Table 1). Some previous studies that have been conducted both in Medan and other countries also show that male NPC sufferers outnumber women with an average ratio of 2-3:1 [17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%